Lung cancer risk among bakers, pastry cooks and confectionary makers: the SYNERGY study. Issue 11 (2nd August 2013) - Behrens, Thomas; Kendzia, Benjamin; Treppmann, Tabea; Olsson, Ann; Jöckel, Karl-Heinz; Gustavsson, Per; Pohlabeln, Hermann; Ahrens, Wolfgang; Brüske, Irene; Wichmann, Hans-Erich; Merletti, Franco; Mirabelli, Dario; et al.
Abstract : Introduction: Some studies have suggested increased lung cancer risks among bakers, however the results overall were inconsistent. The authors studied lung cancer risks among bakers and baking-related occupations in the SYNERGY pooled case–control database from 16 countries. Methods: Occupation in a baking-related job was identified from the subjects' job histories. ORs adjusted for log(age), study centre, smoking behaviour and ever employment in a job with known exposure to occupational lung carcinogens were calculated by unconditional logistic regression. Findings were stratified by sex, histological subtype of lung cancer and smoking status. Results: 19 366 cases (15 606 men) and 23 670 control subjects (18 528 men) were included. 473 cases (415 men, 58 women) and 501 controls (437 men, 64 women) had ever worked in baking or a related job. We did not observe an increased risk for men in baking (OR 1.01; 95% CI 0.86 to 1.18). No linear trends were observed for duration of employment. Some results suggested increased lung cancer risks for women, for example, for working as a baker for >30 years and in never-smokers, but after exclusion of one study these increased risks disappeared. Discussion: The findings from this study do not suggest increased lung cancer risks in baking-related professions.